Pengaruh Motivasi Kerja, Beban Kerja dan Disiplin Kerja Terhadap Kinerja Perawat Ruang Rawat Inap di RSUD Kabupaten Karanganyar - Rochmat Abdul Rosim; Riska Fii Ahsani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The purpose of this study was to analyze the significance of the influence of work motivation, workload and work discipline on the performance of inpatient room nurses at Karanganyar Regency Hospital. This research is a quantitative study at Karanganyar Regency Hospital with a population of 239 inpatient room nurses. The sample was 71 people with proportional cluster random sampling technique. Data collection techniques using questionnaires and observation. Data analysis techniques using multiple linear regression analysis, t test, F test, and coefficient of determination (R2) test. The t test results show that work motivation, workload, work discipline have a significant partial effect on the performance of inpatient room nurses at Karanganyar Regency Hospital. The results of the F test obtained the right model in predicting the effect of work motivation (X1), workload (X2) and work discipline (X3) on nurse performance (Y) in the hospital room of Karanganyar Regency Hospital. Based on the results of the study, it is hoped that the Director will provide opportunities for nurses to participate in education and training and provide rewards proportional to workload, namely medical services according to the number of patients served.